HYDROGEOCHEMICAL AND STABLE ISOTOPE ANALYSIS OF KEBAR HOT SPRINGS MANOKWARI DISTRICT, WEST PAPUA PROVINCE: ANALISIS HIDROGEOKIMIA DAN ISOTOP STABIL MATA AIR PANAS KEBAR KABUPATEN MANOKWARI PROVINSI PAPUA BARAT - Andrew Karubaba; Irwan Iskandar; Syafrizal (INTAN Jurnal Penelitian Tambang, 2023)
In simple terms, geothermal classification is determined according to reservoir equilibrium, fluid type, and temperature. Based on the reservoir temperature, geothermal systems are separated into two different systems: dynamic system (convection) and static system (conduction). This system structure is also affected by topography which is further specified as a high-temperature fluid reservoir. The relationship between the characteristics of the hot springs and geothermal potential is instructive to be analyzed. The objective of the analysis is to determine critical parameters: The chemical composition of the water and the source of origin of the water. Hydrogeochemical studies including analysis of major element analysis; ratio stable isotopes δ18O and δ2H of samples from springs, rivers, and wells used to determine the character of hot springs. The primary element examination shows that the sample ions composition from the hot springs is dominated by three types of rock sources: shale; sandstone; and quartzite rocks. It also reveals that sample hot springs can be considered thermal water (based on the Piper Diagram), and classified as water and rock interactions dominant based on the Gibbs diagram.